Ekstraksi, Karakterisasi dan Daya Penghambatan Kitosan Alami terhadap Jamur Colletotrichum musae secara In Vitro - Tunjung Pamekas; Christanti Sumardiyono; Nursamsi Pusposendjojo; Didik Indradewa (Universitas Gadjah Mada, 2009)
In order to enhance food safety, the use of chemical pesticides on agriculture must be minimized, especially on postharvest processing. One of the alternative ways is the use of natural chitosan. Chitosan has good prospect as an alternative compound to chemical pesticides to be used on postharvest processing for agriculture products which are potential as exported commodity, such as banana cv. Ambon Curup, exotic fruit from Bengkulu. The aims of this research were to extract and characterize chitosan and to evaluate the inhibition of chitosan to Colletotrichum musae. Methods of experiment were (1) extraction of chitosan, (2) characterization of chitosan, and (3) inhibition test of chitosan to the pathogen in vitro. The parameters observed were the growth and colour of colony, the measurement and density of conidia and the dry weight of mycelium. The result indicated that the texture of chitosan were flake-powder with white-brownish colour, had a little bit odor of fish and pH were 7.5–13. The deacetylated degree of chitosan were around 74.27–75.64%. The in vitro test indicated that the kind of chitosan treatments gave no significant effect to the growth and colony colour, the measurement and density of conidia and the dry weight of mycelium. However the concentration of chitosan treatments were significantly effect all parameters. The chitosan on 20 mg/ml could inhibit the colony growth up to 81.20%, the conidial density up to 46.5%, the measurement of conidia up to 19.4%, and the dry weight of mycelium up to 59.46%. Chitosan had no effect to the colour of fungal colony.